Bio-based high-viscosity gel plaster matrix as well as preparation method and application thereof

By using all-natural ingredients and scientific proportioning methods, a bio-based high-viscosity gel paste matrix with excellent adhesion and moisturizing properties was prepared, which solved the insufficient adhesion, moisturizing and permeability promotion in the prior art. The problem of this has achieved efficient and safe patch effects.

CN119405628AActive Publication Date: 2025-02-11云南白药集团无锡药业有限公司 +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411631182.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-11
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing bio-based high-viscosity gel paste matrix has shortcomings in adhesion, moisturizing properties, promoting permeability and distribution of active ingredients, and cannot meet the market's demand for high-quality and high-performance patches.

Method used

All-natural ingredients such as fragrance agents, penetration promoters, moisturizers, crosslinkers, fillers, excipients, gel frameworks, tackifiers, pH regulators and solvents are prepared through scientific proportions and specific processes to form Excellent adhesion and moisturizing properties, and enhances the skin penetration of the drug by promoting penetrants.

Benefits of technology

The long-term stable fit of the patch is achieved, which enhances the deep therapeutic effect of the drug, reduces the risk of skin irritation and allergies, and ensures the even distribution of active ingredients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405628A_ABST
    Figure CN119405628A_ABST
Patent Text Reader

Abstract

The invention provides a bio-based high-viscosity gel plaster matrix, a preparation method of the bio-based high-viscosity gel plaster matrix and a patch containing a simvastatin component. The matrix is prepared from various natural components including dementholized peppermint oil serving as an aromatic, crotamiton and isopropyl myristate serving as penetration promoting agents, glycerin serving as a humectant, a specific cross-linking agent, a filling agent, an excipient, a tackifier and the like through accurate proportioning and a specific process. The composition has excellent adhesion, moisture retention and skin friendliness. Particularly, the tackifier adopts a compound formula of xanthan gum, Arabic gum, guar gum and flaxseed gum, so that the adhesion, the stability and the transdermal effect of the plaster are further improved. On the basis, the invention further provides a patch containing a simvastatin component, the patch is prepared by uniformly mixing simvastatin in a matrix and has a treatment effect, the pharmacological action of simvastatin is exerted, and the use comfort and effect are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of pharmaceutical preparations, and specifically discloses a bio-based high-viscosity gel patch matrix and a preparation method and application thereof. Background Art

[0002] In the medical and health care field, patches are widely used in the treatment and care of various skin diseases as a convenient and effective way of drug delivery. Traditional patch matrices are mostly made of chemically synthesized components. Although they have certain adhesion and drug release properties, they often have disadvantages such as high skin irritation, poor air permeability, and easy allergies, which limits their application range.

[0003] In recent years, with people's pursuit of natural, environmentally friendly and healthy concepts, bio-based high-viscosity gel patch matrices have gradually become a research hotspot. However, there are still some problems with the bio-based gel patch matrices in the prior art. On the one hand, although some matrices use natural ingredients, they are not sufficiently adhesive and cannot ensure that the patch can be stably attached to the skin for a long time, affecting the therapeutic effect; on the other hand, although some matrices have strong adhesion, they have poor moisturizing properties and can easily lead to dry skin, itching and other discomfort reactions. In addition, the patch matrices in the prior art often lack effective permeation promoters, which makes it difficult for drugs to penetrate the skin barrier and achieve deep treatment effects.

[0004] At the same time, in the preparation of patches containing specific active ingredients (such as simvastatin), how to ensure the uniform distribution of the active ingredients in the matrix and avoid excessively high or low local concentrations is also a problem that needs to be solved urgently in the existing technology. Uneven distribution not only affects the therapeutic effect, but also may bring safety risks.

[0005] In summary, the bio-based high-viscosity gel patch matrix in the prior art still has many deficiencies in terms of adhesion, moisturizing, promoting permeability and distribution of active ingredients, and cannot meet the market demand for high-quality and high-performance patches. Summary of the invention

[0006] The present invention provides a bio-based high-viscosity gel patch matrix and a preparation method and application thereof. The matrix has excellent adhesion, good moisture retention, can effectively promote the penetration of active ingredients and can improve the uniform distribution of active ingredients, which is of great significance for improving the therapeutic effect and comfort of the patch.

[0007] The technical solution of the present invention is as follows: A bio-based high-viscosity gel patch matrix, comprising a fragrance, a permeation enhancer 1, a permeation enhancer 2, a moisturizer, a cross-linking agent, a cross-linking regulator, a filler 1, a filler 2, an excipient, a gel skeleton, a viscosity enhancer, a pH regulator and a solvent; The fragrance is peppermint oil; The permeation enhancer 1 is crotamiton, and the permeation enhancer 2 is isopropyl myristate; The viscosity increasing agent is a plant gum, including but not limited to one or more of xanthan gum, gum arabic, guar gum and linseed gum; The filler 1 is titanium dioxide, and the filler 2 is kaolin.

[0008] Furthermore, in the above-mentioned bio-based high-viscosity gel patch matrix, the viscosity enhancer is in a mass ratio of xanthan gum: gum arabic: guar gum: flaxseed gum = 1:1:1:2.

[0009] Furthermore, in the above-mentioned bio-based high-viscosity gel patch matrix, the moisturizer is glycerol; the cross-linking agent is aluminum glycolate; and the cross-linking regulator is disodium edetate.

[0010] Furthermore, in the above-mentioned bio-based high-viscosity gel patch matrix, the excipient is sodium carboxymethylcellulose; the gel skeleton is partially neutralized sodium polyacrylate; and the solvent is purified water.

[0011] Furthermore, in the above-mentioned bio-based high-viscosity gel patch matrix, the partially neutralized sodium polyacrylate is NP700.

[0012] Furthermore, the above-mentioned bio-based high-viscosity gel patch matrix is ​​composed of the following components in parts by weight: Aromatherapy peppermint oil 0.2-1 part Penetration enhancer 1 Crotamiton 0.2-1 part Penetration enhancer 2: 0.2-1 part isopropyl myristate Moisturizer Glycerin 20-40 parts Cross-linking agent aluminum glycolate 0.05-0.2 parts Cross-linking regulator disodium edetate 0.05-0.5 parts Filler 1 Titanium dioxide 0.1-0.5 parts Filler 2 Kaolin 1-5 parts Excipient: 1-5 parts sodium carboxymethylcellulose The gel skeleton is partially neutralized with 5-10 parts of sodium polyacrylate Thickener plant gum 10-20 parts pH adjuster: tartaric acid is used to adjust the pH to 5.0-7.0 The solvent purified water was added to 100 parts.

[0013] The present invention also discloses a method for preparing the above-mentioned bio-based high-viscosity gel patch matrix, comprising the following steps: a) preparing a gel matrix solution: slowly adding and stirring partially neutralized sodium polyacrylate into glycerol until it is completely dispersed to form a uniform gel matrix solution; b) Adding the cross-linking system: adding aluminum glycolate as a cross-linking agent and disodium edetate as a cross-linking regulator to the gel matrix solution, stirring while adding to ensure that the components are evenly dispersed and the stability of the patch is ensured; c) Adding excipients: Add sodium carboxymethyl cellulose as an excipient to the gel matrix solution and continue stirring until it is completely dispersed to promote the formability of the patch; d) Adding fillers: Add titanium dioxide and kaolin as fillers to the gel matrix solution and continue stirring until fully dispersed to improve the spreadability and covering power of the patch; e) Adding fragrance and permeation enhancer: adding peppermint oil, crotamiton and polysorbate 80 to the gel matrix solution, stirring while adding to ensure that the components are evenly dispersed, promote the skin permeation ability of the drug, and provide a better usage experience of the patch; f) Adjusting pH value: dissolving an appropriate amount of tartaric acid in purified water, and adjusting the pH value of the above mixture to 5.0-7.0 to ensure the stability of the product; g) Adding a viscosity enhancer: Dissolve the plant gum in purified water and add it to the above mixture to improve the adhesion and durability of the patch. The plant gum is composed of xanthan gum: gum arabic: guar gum: flaxseed gum = 1:1:1:2; h) Degassing and mixing: The mixed solution is stirred at high speed under vacuum conditions to ensure that all ingredients are fully mixed, and to remove bubbles generated during the stirring process to ensure the fineness and uniformity of the patch. Finally, the bio-based high-viscosity gel patch matrix is ​​obtained.

[0014] The present invention also discloses a patch containing the active ingredient of simvastatin, which is prepared from any of the above-mentioned bio-based high-viscosity gel patch matrix and a therapeutic amount of simvastatin.

[0015] Furthermore, the preparation method of the above-mentioned patch containing simvastatin active ingredient comprises the following steps: S1 Mixing evenly: After the bio-based high-viscosity gel patch matrix is ​​prepared and is still in a stirrable semi-solid state, first dissolve simvastatin in a solvent (polysorbate 80, ethyl oleate), then slowly and evenly add it to the gel patch matrix. Stirring ensures that the active ingredient of simvastatin is evenly distributed in the matrix to avoid excessively high or low local concentrations. S2 Molding and Cutting: The processed gel patch matrix containing the active ingredient of simvastatin is molded into a predetermined shape and size, and is made into a patch through a general patch preparation process.

[0016] Furthermore, in the above-mentioned patch containing the active ingredient of simvastatin, the mass ratio of the bio-based high-viscosity gel patch matrix to simvastatin is 10-100:1; preferably 30-70:1; more preferably 50:1.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a bio-based high-viscosity gel patch matrix and its preparation method and application. The matrix adopts all-natural ingredients, such as plant gum, glycerin, etc., which not only ensures the safety and environmental protection of the product, but also greatly reduces the irritation and allergic risks to the skin. Through scientific proportioning and specific process preparation, the matrix exhibits excellent adhesion and moisturizing properties, can be stably attached to the skin for a long time, and provides a strong guarantee for the effective release of the drug. At the same time, the penetration promoter (crotamiton and isopropyl myristate) in the matrix combined with the plant gum adhesive significantly enhances the skin penetration ability of the drug, so that the drug can penetrate the skin barrier more quickly and achieve the effect of deep treatment.

[0018] In addition, the present invention also discloses a patch containing the active ingredient of simvastatin and using the above-mentioned matrix, the preparation process of which is simple and efficient, ensuring the uniform distribution of simvastatin in the matrix, and avoiding the problem of uneven treatment caused by excessively high or low local concentrations. This patch not only has the unique therapeutic effect of simvastatin, but also combines the high adhesion, moisture retention and permeability promotion of the matrix, making the therapeutic effect more significant and lasting.

[0019] In summary, the bio-based high-viscosity gel patch matrix and the patch containing the simvastatin active ingredient of the present invention have excellent performance in adhesion, moisturizing, promoting permeability, skin friendliness, therapeutic effect and comfort of use, providing a high-quality and high-efficiency new patch product for the medical and health care fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the weight loss test result in the test case, and the Y axis is the water loss rate wt%; Figure 2 It is the test result of the relative transdermal absorption rate in the test example. DETAILED DESCRIPTION

[0021] A bio-based high-viscosity gel patch matrix, composed of the following components in parts by weight: Aromatherapy peppermint oil 0.2-1 part Penetration enhancer 1 Crotamiton 0.2-1 part Penetration enhancer 2: 0.2-1 part isopropyl myristate Moisturizer Glycerin 20-40 parts Cross-linking agent aluminum glycolate 0.05-0.2 parts Cross-linking regulator disodium edetate 0.05-0.5 parts Filler 1 Titanium dioxide 0.1-0.5 parts Filler 2 Kaolin 1-5 parts Excipient: 1-5 parts sodium carboxymethylcellulose The gel skeleton is partially neutralized with 5-10 parts of sodium polyacrylate Thickener plant gum 10-20 parts pH adjuster: tartaric acid is used to adjust the pH to 5.0-7.0 The solvent purified water was added to 100 parts.

[0022] The vegetable gum is composed of xanthan gum: gum arabic: guar gum: linseed gum = 1:1:1:2.

[0023] The method for preparing the above-mentioned bio-based high-viscosity gel patch matrix comprises the following steps: a) preparing a gel matrix solution: slowly adding and stirring partially neutralized sodium polyacrylate into glycerol until it is completely dispersed to form a uniform gel matrix solution; b) Adding the cross-linking system: adding aluminum glycolate as a cross-linking agent and disodium edetate as a cross-linking regulator to the gel matrix solution, stirring while adding to ensure that the components are evenly dispersed and the stability of the patch is ensured; c) Adding excipients: Add sodium carboxymethyl cellulose as an excipient to the gel matrix solution and continue stirring until it is completely dispersed to promote the formability of the patch; d) Adding fillers: Add titanium dioxide and kaolin as fillers to the gel matrix solution and continue stirring until fully dispersed to improve the spreadability and covering power of the patch; e) Adding fragrance and permeation enhancer: adding peppermint oil, crotamiton and polysorbate 80 to the gel matrix solution, stirring while adding to ensure that the components are evenly dispersed, promote the skin permeation ability of the drug, and provide a better usage experience of the patch; f) Adjusting pH value: dissolving an appropriate amount of tartaric acid in purified water, and adjusting the pH value of the above mixture to 5.0-7.0 to ensure the stability of the product; g) Adding a viscosity enhancer: Dissolve the plant gum in purified water and add it to the above mixture to improve the adhesion and durability of the patch. The plant gum is composed of xanthan gum: gum arabic: guar gum: flaxseed gum = 1:1:1:2; h) Degassing and mixing: The mixed solution is stirred at high speed under vacuum conditions to ensure that all ingredients are fully mixed, and to remove bubbles generated during the stirring process to ensure the fineness and uniformity of the patch. Finally, the bio-based high-viscosity gel patch matrix is ​​obtained.

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1 A bio-based high-viscosity gel patch matrix, composed of the following components in parts by weight: 0.2 parts of fragrance peppermint oil Penetration enhancer 1: 0.2 parts of crotamiton Penetration enhancer 2 Myristic acid propyl ester 0.2 parts Moisturizer Glycerin 25 parts Crosslinking agent aluminum glycolate 0.05 parts Cross-linking regulator: 0.08 parts of disodium edetate Filler 1 Titanium dioxide 0.2 parts Filler 2: 1 part kaolin Excipient: 1 part sodium carboxymethylcellulose The gel skeleton is partially neutralized with 5 parts of sodium polyacrylate 10 parts of tackifier vegetable glue pH adjuster: tartaric acid is used to adjust the pH to 5.2 The solvent purified water was added to 100 parts.

[0026] The vegetable gum is composed of xanthan gum: gum arabic: guar gum: flaxseed gum = 1:1:1:2; The method for preparing the above-mentioned bio-based high-viscosity gel patch matrix comprises the following steps: a) preparing a gel matrix solution: slowly adding and stirring partially neutralized sodium polyacrylate into glycerol until it is completely dispersed to form a uniform gel matrix solution; b) Adding the cross-linking system: adding aluminum glycolate as a cross-linking agent and disodium edetate as a cross-linking regulator to the gel matrix solution, stirring while adding to ensure that the components are evenly dispersed and the stability of the patch is ensured; c) Adding excipients: Add sodium carboxymethyl cellulose as an excipient to the gel matrix solution and continue stirring until it is completely dispersed to promote the formability of the patch; d) Adding fillers: Add titanium dioxide and kaolin as fillers to the gel matrix solution and continue stirring until fully dispersed to improve the spreadability and covering power of the patch; e) Adding fragrance and permeation enhancer: adding peppermint oil, crotamiton and polysorbate 80 to the gel matrix solution, stirring while adding to ensure that the components are evenly dispersed, promote the skin permeation ability of the drug, and provide a better usage experience of the patch; f) Adjusting pH value: dissolving an appropriate amount of tartaric acid in purified water, and adjusting the pH value of the above mixture to 5.0-7.0 to ensure the stability of the product; g) Adding a viscosity enhancer: Dissolve the plant gum in purified water and add it to the above mixture to improve the adhesion and durability of the patch. The plant gum is composed of xanthan gum: gum arabic: guar gum: flaxseed gum = 1:1:1:2; h) Degassing and mixing: The mixed solution is stirred at high speed under vacuum conditions to ensure that all ingredients are fully mixed, and to remove bubbles generated during the stirring process to ensure the fineness and uniformity of the patch. Finally, the bio-based high-viscosity gel patch matrix is ​​obtained.

[0027] Example 2 A bio-based high-viscosity gel patch matrix, composed of the following components in parts by weight: 0.2 parts of fragrance peppermint oil Penetration enhancer 1 Crotamiton 0.5 parts Penetration enhancer 2: 0.2 parts of isopropyl myristate Moisturizer Glycerin 28 parts Crosslinking agent aluminum glycolate 0.08 parts Cross-linking regulator disodium edetate 0.1 part Filler 1 Titanium dioxide 0.2 parts Filler 2: 1 part kaolin Excipient: 2 parts sodium carboxymethylcellulose The gel skeleton is partially neutralized with 6 parts of sodium polyacrylate 15 parts of tackifier vegetable glue pH adjuster: tartaric acid is used to adjust the pH to 5.5 Solvent: 100 parts of purified water.

[0028] The preparation is the same as Example 1.

[0029] Example 3 A bio-based high-viscosity gel patch matrix, composed of the following components in parts by weight: 0.2 parts of fragrance peppermint oil Penetration enhancer 1 Crotamiton 0.5 parts Penetration enhancer 2: 0.5 parts of isopropyl myristate Moisturizer Glycerin 35 parts Crosslinking agent aluminum glycolate 0.15 parts Cross-linking regulator disodium edetate 0.2 parts Filler 1 Titanium dioxide 0.2 parts Filler 2: 1 part kaolin Excipient: 3 parts of sodium carboxymethylcellulose Gel skeleton partially neutralized with 8 parts of sodium polyacrylate 20 parts of tackifier vegetable glue pH adjuster: tartaric acid is used to adjust the pH to 5.7 Solvent: 100 parts of purified water.

[0030] The preparation is the same as Example 2.

[0031] Example 4 The vegetable gum is composed of xanthan gum: gum arabic: guar gum: linseed gum = 1:1:1:1, and the rest is the same as in Example 2.

[0032] Example 5 The vegetable gum is composed of xanthan gum: gum arabic: guar gum: linseed gum = 1:1:1:3, and the rest is the same as in Example 2.

[0033] Comparative Example 1 Compared with Example 2, the plant gum is composed of xanthan gum: gum arabic: guar gum = 1:1:1.

[0034] Comparative Example 2 Compared with Example 2, the plant gum consists of xanthan gum: gum arabic = 1:1.

[0035] Comparative Example 3 Compared with Example 2, the plant gum is xanthan gum.

[0036] Comparative Example 4 Compared with Example 2, a chemical thickener (20% polyacrylic acid solution produced by Toagosei Co., Ltd.) was used.

[0037] Test Example 1 Embodiment 1-5, comparative example 1-4 gel patch matrix, according to the routine preparation into 3x3cm square patch, containing matrix 5g, each experimental sample, affixed to the outer side of the upper arm of volunteer subjects, a total of 25, kept for 8h, film residue, skin follow-up, use comfort, skin irritation, skin allergy, tearing pain, etc. were evaluated, divided into good, medium, poor, three types, good is 5 points, good is 3 points, medium is 1 point, poor is 0 point, the cumulative sum is divided by the number of subjects, retaining 1 decimal place, the results are shown in Table 1.

[0038] Table 1 Subjective evaluation Film Residue Skin following Comfort Skin irritation Skin allergy tearing pain Example 1 4.8 4.7 4.7 4.8 4.8 4.5 Example 2 4.9 4.6 4.6 4.8 4.9 4.6 Example 3 4.7 4.8 4.6 4.9 4.7 4.6 Example 4 4.3 4.4 4.1 4.9 4.8 4.6 Example 5 4.2 4.3 4.2 4.8 4.9 4.5 Comparative Example 1 3.8 3.8 3.7 4.7 4.8 4.6 Comparative Example 2 3.5 3.6 3.5 4.8 4.7 4.5 Comparative Example 3 3.1 3.4 3.5 4.6 4.7 4.6 Comparative Example 4 3.7 3.5 3.6 3.8 3.5 3.2 From the above examples, it can be seen that Examples 1-5 and Comparative Examples 1-3 using plant gums are significantly better than similar products using chemical tackifiers in terms of skin irritation, skin allergy and tearing pain. From the comparison between the examples and the comparative examples, it can be seen that the combined effect of using xanthan gum, gum arabic, guar gum and linseed gum as plant gums is better than the combined effect of Comparative Examples 1-3; from the comparison between Example 2 and Example 4 and Example 5, it can be seen that when the mass ratio of xanthan gum: gum arabic: guar gum: linseed gum is maintained at 1:1:1:2, the best film residue, skin followability and use comfort evaluation can be obtained.

[0039] Test Example 2 Initial adhesion performance test (30° slope rolling ball method), samples: Examples 1-5 and Comparative Examples 1-4 samples, prepare patches according to the method of Test Example 1: Adhesion was measured according to General Rules 0952 of Part IV of the Chinese Pharmacopoeia 2020 Edition, and the results are shown in Table 2.

[0040] Table 2 Initial adhesion performance test Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Initial adhesion (30°) No. 17 steel ball No. 20 steel ball No. 18 steel ball No. 17 steel ball No. 16 steel ball No. 14 steel ball No. 12 steel ball No. 10 steel ball No. 16 steel ball It can be seen from Table 2 above that the initial adhesion is best when a mixed vegetable gum of xanthan gum, gum arabic, guar gum and linseed gum is used, and the best initial adhesion can be obtained when the mass ratio of gum arabic: guar gum: linseed gum is maintained at 1:1:1:2.

[0041] Test Example 3 Weightlessness test Samples: Examples 1-5 and Comparative Examples 1-4 samples, patches were prepared according to the method of Test Example 1.

[0042] Method: Take the trial samples and store them in an indoor environment with a temperature of 20℃ and a humidity of 50%. Measure their weight loss and examine their water retention and stability. The weight loss is calculated as wt%.

[0043] Results Figure 1 And as shown in Table 3.

[0044] Table 3 Weightlessness test Wt% Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 1 day 0.23 0.21 0.19 0.26 0.28 0.33 0.35 0.36 0.51 3 days 0.43 0.41 0.37 0.48 0.58 0.62 0.65 0.71 0.97 5 days 0.87 0.83 0.75 0.97 1.03 1.24 1.34 1.52 1.98 10 days 1.45 1.35 1.28 1.53 1.56 1.98 2.11 2.16 2.54 It can be seen from Table 3 above that the water loss weight of Example 2 in 10 days is only 1.28wt%, which is much lower than the water loss value of the comparative example. It can be seen that the combination of plant gums xanthan gum, gum arabic, guar gum and linseed gum not only has strong adhesiveness, but also has good moisturizing properties.

[0045] Test Example 4 Simvastatin (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) was dissolved in a solvent such as polysorbate and ethyl oleate, and added into the matrix of Examples 1-5 and Comparative Examples 1-4 according to the following steps to prepare a medicinal patch.

[0046] S1 Mixing evenly: After the bio-based high-viscosity gel patch matrix is ​​prepared and is still in a stirrable semi-solid state, first dissolve simvastatin in a solvent (polysorbate 80, ethyl oleate), then slowly and evenly add it to the gel patch matrix. Stirring ensures that the active ingredient of simvastatin is evenly distributed in the matrix to avoid excessively high or low local concentrations. S2 Molding and Cutting: The processed gel patch matrix containing the active ingredient of simvastatin is molded into a predetermined shape and size, and is made into a patch through a general patch preparation process.

[0047] The mass ratio of the bio-based high-viscosity gel patch matrix to simvastatin is 50:1.

[0048] The above-prepared medicinal patch was subjected to a transdermal absorption test: Instruments: Transdermal absorption diffusion instrument (PermeGear In-Line Cells, PermeGear online automatic transdermal diffusion system), liquid chromatography Test steps (1) Take the processed miniature pig skin sample and soak it in physiological saline for 2 h.

[0049] (2) Cut the skin sample into appropriate size, apply the test sample on the outside with a thickness of 1 mm, and fix it on the Franz diffusion cell (with the inside of the skin sample facing the diffusion liquid). Connect and fix the supply cell and the receiving cell. Add the receiving liquid preheated to 32°C into the receiving cell.

[0050] (3) Place the diffusion cell with the fixed sample in a transdermal diffusion instrument water bath preheated to 32°C and stir magnetically at 50 rpm.

[0051] (4) Take a sample after 8 hours and take out 1 ml of the receiving solution.

[0052] (5) Sampling was carried out on a high performance liquid chromatograph for testing and analysis (the transdermal water absorption rate was calculated based on the peak area of ​​simvastatin reference substance, and the transdermal water absorption rate of comparative example 5 was used as the basis (1.0) to calculate the relative transdermal water absorption rate (SPR) of other examples).

[0053] Results Figure 2 And as shown in Table 4.

[0054] Table 4 Relative transdermal absorption rate SPR Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 8h 1.74 1.78 1.77 1.65 1.58 1.32 1.25 1.17 1.0 It can be seen from the data in Table 4 that the transdermal absorption rate of Example 2 is increased by nearly 80% compared with that of Comparative Example 4, indicating that the use of plant gum, preferably a combination of xanthan gum, gum arabic, guar gum and flaxseed gum, has a better effect of promoting drug penetration through the skin than chemical thickeners, and is more likely to exert its efficacy.

[0055] It can be seen from the above example data that the present invention discloses a bio-based high-viscosity gel patch matrix and its preparation method and application. The matrix adopts all-natural ingredients, such as plant gum, glycerin, etc., which not only ensures the safety and environmental protection of the product, but also greatly reduces the irritation and allergic risks to the skin. Through scientific proportioning and specific process preparation, the matrix exhibits excellent adhesion and moisturizing properties, can be stably attached to the skin for a long time, and provides a strong guarantee for the effective release of the drug. At the same time, the penetration promoter (crotamiton and polysorbate 80) in the matrix combined with the plant gum adhesive can significantly enhance the skin penetration ability of the drug, so that the drug can penetrate the skin barrier more quickly and achieve the effect of deep treatment.

[0056] The above are only a few preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A bio-based high-viscosity gel patch matrix, characterized in that: The composition comprises a fragrance, a permeation enhancer 1, a permeation enhancer 2, a moisturizer, a cross-linking agent, a cross-linking regulator, a filler 1, a filler 2, an excipient, a gel skeleton, a viscosity enhancer, a pH regulator and a solvent; The fragrance is peppermint oil; The penetration enhancer 1 is crotamiton, and the penetration enhancer 2 is isopropyl myristate; The viscosity increasing agent is a plant gum, including but not limited to one or more of xanthan gum, gum arabic, guar gum and linseed gum; The filler 1 is titanium dioxide, and the filler 2 is kaolin.

2. A bio-based high-viscosity gel patch matrix according to claim 1, characterized in that: The mass ratio of the thickener is xanthan gum: gum arabic: guar gum: linseed gum = 1:1:1:

2.

3. A bio-based high-viscosity gel patch matrix according to claim 1, characterized in that: The moisturizing agent is glycerin; the cross-linking agent is aluminum glycolate; and the cross-linking regulator is disodium edetate.

4. The bio-based high-viscosity gel patch matrix according to claim 1, characterized in that: The excipient is sodium carboxymethylcellulose; the gel skeleton is partially neutralized sodium polyacrylate; and the solvent is purified water.

5. A bio-based high-viscosity gel patch matrix according to claim 4, characterized in that: The partially neutralized sodium polyacrylate is NP700.

6. The bio-based high-viscosity gel patch matrix according to claim 1, characterized in that: By weight, it is composed of the following ingredients: Aromatherapy peppermint oil 0.2-1 part Penetration enhancer 1 Crotamiton 0.2-1 part Penetration enhancer 2: 0.2-1 part isopropyl myristate Moisturizer Glycerin 20-40 parts Cross-linking agent aluminum glycolate 0.05-0.2 parts Cross-linking regulator disodium edetate 0.05-0.5 parts Filler 1 Titanium dioxide 0.1-0.5 parts Filler 2 Kaolin 1-5 parts Excipient: 1-5 parts sodium carboxymethylcellulose The gel skeleton is partially neutralized with 5-10 parts of sodium polyacrylate Thickener plant gum 10-20 parts pH adjuster: tartaric acid is used to adjust the pH to 5.0-7.0 The solvent purified water was added to 100 parts.

7. The method for preparing the bio-based high-viscosity gel patch matrix according to claim 6, characterized in that: The following steps are involved: a) preparing a gel matrix solution: slowly adding and stirring partially neutralized sodium polyacrylate into glycerol until it is completely dispersed to form a uniform gel matrix solution; b) Adding the cross-linking system: adding aluminum glycolate as a cross-linking agent and disodium edetate as a cross-linking regulator to the gel matrix solution, stirring while adding to ensure that the components are evenly dispersed and the stability of the patch is ensured; c) Adding excipients: Add sodium carboxymethyl cellulose as an excipient to the gel matrix solution and continue stirring until it is completely dispersed to promote the formability of the patch; d) Adding fillers: Add titanium dioxide and kaolin as fillers to the gel matrix solution and continue stirring until fully dispersed to improve the spreadability and covering power of the patch; e) Adding fragrance and permeation enhancer: adding peppermint oil, crotamiton and polysorbate 80 to the gel matrix solution, stirring while adding to ensure that the components are evenly dispersed, promote the skin permeation ability of the drug, and provide a better usage experience of the patch; f) Adjusting pH value: dissolving an appropriate amount of tartaric acid in purified water, and adjusting the pH value of the above mixture to 5.0-7.0 to ensure the stability of the product; g) Adding a viscosity enhancer: dissolving plant gum in purified water and adding it to the above mixture to improve the adhesion and durability of the patch; the plant gum is composed of xanthan gum: gum arabic: guar gum: linseed gum = 1:1:1:2; h) Degassing and mixing: The mixed solution is stirred at high speed under vacuum conditions to ensure that all ingredients are fully mixed and to remove bubbles generated during the stirring process to ensure the fineness and uniformity of the patch, thereby finally obtaining the bio-based high-viscosity gel patch matrix.

8. A patch containing simvastatin as an active ingredient, characterized in that: The invention is prepared from the bio-based high-viscosity gel patch matrix as claimed in any one of claims 1 to 7 and a therapeutic amount of simvastatin.

9. A patch containing simvastatin as an active ingredient according to claim 8, characterized in that: Prepared by the following steps: S1. Mixing evenly: After the bio-based high-viscosity gel patch matrix is ​​prepared and is still in a stirrable semi-solid state, simvastatin is first dissolved in a solvent; the solvent is polysorbate 80 and ethyl oleate; the solvent is slowly and evenly added to the gel patch matrix, and stirred to ensure that the active ingredient of simvastatin is evenly distributed in the matrix to avoid excessively high or low local concentrations; S2 Molding and Cutting: The processed gel patch matrix containing the active ingredient of simvastatin is molded into a predetermined shape and size, and is made into a patch through a general patch preparation process.

10. A patch containing simvastatin as an active ingredient according to claim 8, characterized in that: The mass ratio of the bio-based high-viscosity gel patch matrix to simvastatin is 10-100:1.

Citation Information

Patent Citations

  • Transdermal drug delivery system

    CN111315438A

  • Micro-emulsified high-viscosity stable gel plaster matrix and preparation method thereof

    CN115501210A

  • Plaster for transcutaneous administration

    JP1987116509A

  • Clonidine dermal administration pharmaceutical preparation

    JP1993279254A

  • High adhesive hydrogel composition containing lambda carrageenan

    KR1020140029897A